Impact of Psychological Barriers and learned Helplessness on Language Proficiency - Gul, Shazia (The Lighthouse Journal of Social Sciences, 2024)
Learning of English language in government institutions where Urdu is the primary medium of instruction is a perpetual challenge for students. This linguistic barrier drastically impacts student’s communication and comprehension skills, and hampers their academic performance and confidence. To better understand these challenges, the current study examines how psychological barriers and learned helplessness impact English language proficiency among 100 randomly selected female students, enrolled in semester II of Govt. Girls Degree College Sarai Salah, Haripur. Data were collected by using Psychological Barrier Questionnaire, Learned Helplessness Scale, and Interagency Language Round table Scale. The findings demonstrated weak, negative correlation between Psychological Barriers, Learned Helplessness and English proficiency, while a weak positive relationship emerged between learned helplessness and psychological barriers. Although none of these correlations reached statistical significance, they suggest meaningful directional trends. The regression analysis shows a statistically significant negative impact of Learned Helplessness on Language proficiency, indicating that greater helplessness correlates with lower proficiency. These results accentuate dire need to address the psychological and contextual factors to maximize student’s language proficiency.